Methods used for immunization coverage assessment in Canada, a Canadian Immunization Research Network (CIRN) study. Issue 8 (3rd August 2017) - Wilson, Sarah E.; Quach, Susan; MacDonald, Shannon E.; Naus, Monika; Deeks, Shelley L.; Crowcroft, Natasha S.; Mahmud, Salaheddin M.; Tran, Dat; Kwong, Jeff; Tu, Karen; Gilbert, Nicolas L.; Johnson, Caitlin; et al.
ABSTRACT: Accurate and complete immunization data are necessary to assess vaccine coverage, safety and effectiveness. Across Canada, different methods and data sources are used to assess vaccine coverage, but these have not been systematically described. Our primary objective was to examine and describe the methods used to determine immunization coverage in Canada. The secondary objective was to compare routine infant and childhood coverage estimates derived from the Canadian 2013 Childhood National Immunization Coverage Survey (cNICS) with estimates collected from provinces and territories (P/Ts). We collected information from key informants regarding their provincial, territorial or federal methods for assessing immunization coverage. We also collected P/T coverage estimates for select antigens and birth cohorts to determine absolute differences between these and estimates from cNICS. Twenty-six individuals across 16 public health organizations participated between April and August 2015. Coverage surveys are conducted regularly for toddlers in Quebec and in one health authority in British Columbia. Across P/Ts, different methodologies for measuring coverage are used (e.g., valid doses, grace periods). Most P/Ts, except Ontario, measure up-to-date (UTD) coverage and 4 P/Ts also assess on-time coverage. The degree of concordance between P/T and cNICS coverage estimates varied by jurisdiction, antigen and age group. In addition to differences in the data sources and processes used for coverage assessment, there are also differences between Canadian P/Ts in the methods used for calculating immunization coverage. Comparisons between P/T and cNICS estimates leave remaining questions about the proportion of children fully vaccinated in Canada.